Evaluación de la adición de harina de zanahoria (Daucus carota L.) como aditivo alimenticio en la dieta de pollos camperos desde la etapa de crecimiento - Fernandez Silva, Genesis Micaela (2024)
The following research presents the use of carrot flour as a food additive in the diet of free range chickens, as an alternative for improving pigmentation and production, using natural products and not pigments that are synthetic. The objective of the study was to evaluate the different treatments used for carrot flour (Daucus carota L.) and identify the most optimal one based on the productive behavior of the chickens, in addition to an analysis of blood carotenes and colorimetric index through digital colorimeter that verifies the use of this additive in your food. The experimental phase of this research was carried out at the facilities of the ECAA Experimental farm (School of Agricultural and Environmental Sciences) in the city of Ibarra. In this study, it was carried out under a DCA experimental model with 4 treatments and 3 repetitions in which 120 free-range chickens of 15 days of age were used, which were randomly distributed in 12 different groups with 10 chickens/m2 in each one. To establish the effectiveness of the most appropriate treatment, the ANOVA and Tukey's test at 5% were used, in this way the differences between each treatment and the effectiveness in productivity were found. Once the experiment is completed, the effectiveness of using carrot flour in feeding the chickens can be demonstrated, benefiting the parameters that were evaluated, reducing the period of release of the free-range chicken with a weight of 3653.66g (T1), This is due to an improvement in feed conversion, in which 1,15 was obtained as a better result for T1 with 5% carrot flour. This addition demonstrates its profitability, using natural pigments that are not harmful to health and being more desirable to the consumer.